Cervical carotid artery vasospasm during cerebral angiography - Mustafa Ismail; Muthanna N. Abdulqader; Fatimah O. Ahmed; Aktham O. Al-Khafaji; Hosam Al-Jehani; Samer S. Hoz (Romanian Neurosurgery, 2022)
Background: Vasospasm occurs commonly in the intracranial arteries as a complication of subarachnoid haemorrhage. On the other hand, extracranial Internal carotid artery (ICA) vasospasm is scarce, and it may occur due to mechanical manipulation during cerebral angiography. We report a case of cervical carotid artery vasospasm during diagnostic cerebral angiography, which caused anterior cerebral artery territory hypoperfusion, to discuss potential risk factors.